2022
DOI: 10.1111/jch.14487
|View full text |Cite
|
Sign up to set email alerts
|

Differences of blood pressure measured at clinic versus at home in the morning and in the evening in Europe and Asia: A systematic review and meta‐analysis

Abstract: Numerous studies have indicated that there might be great differences among different populations in Europe and Asia in terms of home morning and evening blood pressure (BP). Thus, the authors performed a systematic review to determine the quantitative differences of BP measured at clinic versus at home in the morning and in the evening in Europe and Asia. PubMed, Embase, and Scopus databases were searched up to October 2021. Studies that compared clinic BP with home morning and (or) home evening BP in Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(263 reference statements)
1
4
0
Order By: Relevance
“…In the parallel analysis comparing AOBP measurements with the assistance of an instructional video and morning HBP, similar values were derived. AOBP and morning HBP have good agreement with morning ABP [25], although the diurnal change in BP should be considered such that morning HBP is higher than evening HBP in studies conducted in Asia, whereas the values are comparable in European studies [26]. The result of the present study, in which all participants were Asian had concordance with the result of a smaller difference between clinic BP and morning HBP obtained in the previous study [26].…”
Section: Discussionsupporting
confidence: 85%
“…In the parallel analysis comparing AOBP measurements with the assistance of an instructional video and morning HBP, similar values were derived. AOBP and morning HBP have good agreement with morning ABP [25], although the diurnal change in BP should be considered such that morning HBP is higher than evening HBP in studies conducted in Asia, whereas the values are comparable in European studies [26]. The result of the present study, in which all participants were Asian had concordance with the result of a smaller difference between clinic BP and morning HBP obtained in the previous study [26].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the difference between home-measured SBP and clinic SBP was much larger (i.e. higher) in Europeans than Asians when measured in the morning [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the mean difference in SBP readings was 20.46 mmHg, which is higher than the international norm. A systematic review and meta-analysis [ 21 ] also identified disparities between clinic and home SBP values, with mean clinic SBP values being significantly higher than MHSBP values, by 3.79 mmHg (95% CI, 2.77–4.80). The differences were more pronounced in Europe (6.53 mmHg (95% CI, 4.10–8.97)) than in Asia (2.70 mmHg (95% CI, 1.74–3.66)), with the region being a significant predictor of differences [ 22 ].…”
Section: Discussionmentioning
confidence: 99%